Assume $F$ is a field of zero characteristic. Denote the elementary symmetric polynomials of $n$ variables by $e_k$, $\quad k=\overline{1,n}$. Let the symbol $\sum ax_1^{i_1}\dots x_n^{i_n}$ denote the sum of all different monomials which can be obtained from $ax_1^{i_1}\dots x_n^{i_n}$ by permuting its variables. For instance, if $n=3$,

$$\sum x_1^2x_2=x_1^2x_2+x_1^2x_3+x_2^2x_1+x_2^2x_3+x_3^2x_1+x_3^2x_2$$

The polynomials $S_k=\sum_{i=1}^n x_i^k$ are called power sum symmetric polynomials. Obviously $S_1=e_1$ and $S_2=e_1^2-2e_2$. In order to prove Newton's identities one can see that for $2<k<n+1$

$$e_iS_{k-i}=\sum x_1^{k-i+1}x_2\dots x_i+\sum x_1^{k-i}x_2\dots x_ix_{i+1}$$

How can we see the above identity?

  • $\begingroup$ Does it help to consider the relation $1 + e_1 + \dots + e_n = (1+x_1)(1+x_2)\dots(1+x_n)$? $\endgroup$
    – bryanj
    Jun 23, 2014 at 12:30

1 Answer 1


EDIT: I don't think I answered the precise question that you asked, but instead sketched another proof of Newton's relations.

If you're talking about this,
then consider the relation $1 + e_1 + \dots + e_n = (1+x_1)(1+x_2)\dots(1+x_n)$.

For an indeterminate $t$, you get:
$t^n + t^{n-1} e_1 + \dots + t^0 e_n = (t+x_1)(t+x_2)\dots(t+x_n)$

Substitute $t = -x_k$:
$(-1)^n x_k^n + (-1)^{n-1} x_k^{n-1} e_1 + \dots + e_n = 0$

Do this for all $x_k$, $k = 1, \dots, n$ and sum:

$(-1)^n (x_1^n + \dots + x_n^n) + (-1)^{n-1} (x_1^{n-1} + \dots + x_n^{n-1})e_1 + \dots + n e_n = 0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.